2019
DOI: 10.1088/1757-899x/620/1/012116
|View full text |Cite
|
Sign up to set email alerts
|

The analysis of the dimple arrangement of the artificial hip joint to the performance of lubrication

Abstract: Artificial hip joint surgery is one of the most successful methods used to restore the functioning of damaged hip bones. But there are obstacles to the use of artificial hip bone, which is the amount of friction occurring and wears. To overcome these obstacles, a surface of the artificial hip joint is modified by adding dimples in order to minimize the contact pressure of solid and to reduce friction and wear. The purpose of this study is to determine a better of lubrication performance with the variations of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 32 publications
1
19
0
Order By: Relevance
“…Furthermore, as shown in Figure 9 , the textured surface can withstand local wear, as evidenced by the distribution of the contact pressure after 2 × 10 6 cycles, which was not too wide compared to the model without dimples. The explanation for the results presented is consistent with the available literature, which suggests various positive effects of textured surface applications on contact surfaces [ 9 , 10 , 12 , 13 , 14 ].…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…Furthermore, as shown in Figure 9 , the textured surface can withstand local wear, as evidenced by the distribution of the contact pressure after 2 × 10 6 cycles, which was not too wide compared to the model without dimples. The explanation for the results presented is consistent with the available literature, which suggests various positive effects of textured surface applications on contact surfaces [ 9 , 10 , 12 , 13 , 14 ].…”
Section: Resultssupporting
confidence: 90%
“…Total hip arthroplasty with a textured surface can reduce the surface contact area, and decrease the adhesion wear and coefficient of friction [ 8 ]. Dimples serve to trap wear particles, thereby preventing abrasive wear of the contact surface by a third object, and generating hydrodynamic pressure to provide additional lift [ 9 , 10 ]. Various studies have also shown the positive effect of surface texturing on bearings in improving the tribological performance, both theoretically and experimentally [ 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations